A Filosofia da religião árabe: linhas gerais - ter Reegen, Jan Gerard Joseph (Kairós: Revista Acadêmica da Prainha, 2021)
This paper tries to design the outlines of a philosophy of Arabic Religion. Regarding the region wherein this Religion appeared and developed its main and fundamental lines, inspired by the angel Gabriel’s message to Mohamad, are developed the questions and inspiration of Islamic life and religion.